Las exportaciones de minerales en el Perú de cara al bicentenario: análisis económico, proyección estadística y perspectivas para el mediano plazo - Cano, Jannet (2018)
Given the importance of the external sector in the evolution of the Peruvian economy, this paper analyzes export characteristics in the 1950-2016 period. Additionally, using monthly time series data for the 2009-2017 period, we forecast these exports through 2021, for which we take into account their link their respective prices and volumes, in the case of the four main metals this country exports.After characterizing the series based on volatility analysis and unit root tests, forecasts are made based on a statistical trend curve. The results show growing trends that would contribute to greater export value.